Access of arylmethanes via iridium-catalyzed deoxygenative cross-coupling of aryl ketones with anilines/phenols - Ouyang, Lu; Liang, Yuqiu; Wang, Sen; Liao, Jianhua; Luo, Renshi (Journal of catalysis, 2024)
[Display omitted] •Deoxygenative cross-coupling of aryl ketones with anilines/phenols was established.•Diverse anilines, phenols, and arylketones were compatible with this catalytic system.•Applications of bioactive molecules verified potential practicality of this method.•This strategy merits attention regioselectivity, scalability and practicability. Construction of arylmethanes is one of the forefronts and significant subjects in the field of organic synthesis due to the prevalence of this motifs in pharmaceuticals and biological compounds. Herein, an iridium-catalyzed deoxygenative cross-coupling of aryl ketones with anilines/phenols was established to synthesize diverse collections of arylmethanes. This process generates benzyl carbocationic intermediates from a wide range of aryl ketones, which were captured with anilines/phenols to access the corresponding arylmethanes under mild conditions. The fluorene compounds were also successfully afforded using ortho-substituted aryl ketones as inputs via intermolecular deoxygenative cross-coupling. This method is viable for applications in cross-coupling of complex bioactive molecules and drugs by this iridium-catalyzed deoxygenative cross-coupling process.